2015
DOI: 10.1590/0037-8682-0011-2015
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility characterization of residual Brazilian populations of Triatoma infestans Klug, 1834 (Hemiptera: Reduviidae) to deltamethrin pyrethroid

Abstract: The results of this study indicate that the persistence of residual foci of T. infestans in Bahia and Rio Grande do Sul is not related to insecticide resistance but may be associated with operational failures. In Rio Grande do Sul, we must consider the possibility of continuous reinfestation by Argentinian individuals, which justifies active and efficient epidemiological surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
1
5
0
5
Order By: Relevance
“…We observed house-invading P. megistus in few residences, and T. infestans occurred in one municipality in our study (Novo Horizonte); T. infestans were also recorded in other two municipalities in Bahia in the last years (Ibipeba and Tremedal) [15, 30, 31]. These results show the success in controlling domestic triatomines with the virtual elimination of T. infestans in Bahia municipalities [32, 33].…”
Section: Discussionsupporting
confidence: 60%
“…We observed house-invading P. megistus in few residences, and T. infestans occurred in one municipality in our study (Novo Horizonte); T. infestans were also recorded in other two municipalities in Bahia in the last years (Ibipeba and Tremedal) [15, 30, 31]. These results show the success in controlling domestic triatomines with the virtual elimination of T. infestans in Bahia municipalities [32, 33].…”
Section: Discussionsupporting
confidence: 60%
“…With respect to spraying, it has been reported that insect resistance to the chemical treatment employed (pyrethroid insecticides such as alpha-cypermethrin and deltamethrin) was not observed. In addition, Pessoa et al (2015) 14 and Belisário et al (2017) 15 demonstrated that the specimens of T. infestans strong genetic structure and little to no gene flow among populations, from the states of Bahia and RS, collected precisely in Santa Rosa and Doutor Maurício Cardoso. These municipalities, together with Santo Cristo, exhibited the last foci of T. infestans in this investigation and were susceptible to pyrethroid insecticide deltamethrin in laboratory tests, corroborating our field observations.…”
mentioning
confidence: 99%
“…However, the different toxicological profi les of deltamethrin in T. sordida populations from distinct locations in the same municipality (e.g., Frutal/Guilherme F. Correa and Frutal/ Aureliano N. Cruz), showed the complexity of the resistance phenotype, at both macro-and microgeographical levels, as observed by Pessoa et al (16) in their studies of Brazilian T. infestans populations from Rio Grande do Sul. They observed that deltamethrin does not present homogenous effects over different populations from the same locality, suggesting independent selection pressure.…”
Section: Ethical Considerationsmentioning
confidence: 77%